Can the use of a free mobile phone inclinometer application improve the accuracy of coronal cup position during total hip arthroplasty? - Bibek Banskota; Rajendra Aryal; Ansul Rajbhandari; Deependra Yadav; Ashok K. Banskota (Journal of Orthopaedic Reports)
Background: Accurate acetabular cup positioning during THA has essential implications for function and long-term prosthesis survival. Low-volume hip arthroplasty surgeon is known to be a risk factor for malpositioning of the acetabular cup. Also, even in a low-volume setting, the surgeon may be required to perform hip arthroplasty for complex primary or revision cases. Thus, any adjunct that has the potential to improve accuracy during surgery should be encouraged to avoid cup malposition and its long-term problems. Methods: A year-long (Jan-2021 to Jan-2022) descriptive cross-sectional study was carried out on all patients receiving primary total hip arthroplasty (THA) at B&B hospital. Results: There were 36 patients (36 hips) with an average age of 48.53 years (SD 48.53 ± 15.02). There were 21 (58.33 %) males and 15 (41.67 %) females, and the right and left hips were involved in 18 patients each. All acetabular cups were uncemented. The inferential analysis indicated no statistically significant difference in the measurements obtained through the two methods, as reflected by a p-value of 0.99 at a 95 % confidence interval. Conclusion: The present study compared the values of acetabular inclination measured during surgery using a mobile phone inclinometer application with post-operative values calculated using a standard anteroposterior radiograph of the pelvis to ascertain if the inclinometer app is reliable in predicting the final acetabular inclination. We believe this will provide the surgeon with a safeguard during surgery to achieve the desired acetabular cup inclination.